(untitled) (Global Journal of Science Frontier Research, 2017)
Einstein’s special relativity theory published in 1905 was really based not on two principles, but on three principles. The first principle was the principle of relativity (Einstein’s first postulate). The so called second Einstein’s postulate can be separated in two independent principles: 1. Light emitted by a source being at rest in a "stationary" inertial reference frame moves in this frame at the speed 0 с = 299792458 m/s; 2. Light speed in a "moving" inertial reference frame is also equal to the same value 0 с . My purpose consists in decreasing number of Einstein’s postulates by refusal from the law of independence of light speed upon light source speed that is actually the third Einstein’s principle. Equality of time measurement units in two light clocks of identical design moving each with respect another one uniformly and rectilinearly is a consequence from the relativity principle and this equality discards the moving clock retardation with respect to a stationary clock. Logunov’s method is used for deriving new transformation instead of Lorentzian one. My theory based on two principles (relativity principle and the PACS:03.30.+p, 06.30.Gv 2 principle of light speed in a stationary inertial reference frame from an immovable source) does not forbid superlight speeds. Besides the known Lorentzian speed of particles motion, the Galilean speed varying from zero to infinity is used. Instead of independence of particle electrical charge value resulting from Lorentzian transformation, a law of dependence of particle electrical charge value upon particle speed is derived. The experiment by Neddermeyer and Anderson in 1938 is interpreted as a confirmation of superlight speeds and dependence of electric charge upon particles speed existence in nature. Formulas of new particle dynamics are derived from new theory transformation.